Femoral Orthopedic Implants in Dogs with Titanium - Mechanical Evaluation - Carvalho de Souza, Thiago Henrique; Morales, Isabella Cristina; Pinheiro Denevitz, Rodiney; Antunes, Fernanda; Atem, Eduardo; Saboya, Fernando; Silva, Rodrigo Luis; Ribeiro Menezes, Marcos Felipe; Peters Scheffer, Jussara; Oliveira, André Lacerda de Abreu (Acta Scientiae Veterinariae, 2022)
ABSTRACT Background: Orthopedic implants are commonly used for different types of surgical procedures to gain optimal function and to provide stability to both bones and tendon structures. When inserting these implants, the characteristics of the material are important for surgical success, and the ideal implant must be biocompatible and nonallergenic. However, when molding an implant to the bone structure, its resistance can change significantly. Implants can be temporary or permanent in the body, and metal possesses properties that make it acceptable for bone repair. In biomedical implants, 2 types are most common, commercially pure (CP)-Ti and Ti-6A1-4V. They both provide stable fixation and low risk of loosening. Implants made with the same material and composition can perform differently if the material has been altered by processing techniques for different scenarios. Stress, strain and elastic modulus are the primary metrics used in the description of implant materials. They can be calculated based on mechanical tests of specimens with defined geometry, most commonly tensile, bending and torsional tests. In order to better evaluate those changes, we compared the mechanical characteristics of titanium bone plates, before and after they were molded to the bone, to verify and quantify the loss of stiffness and resistance after molding the plate. Materials, Methods & Results: The study was prospective. Orthopedic implant made of commercially pure titanium (CP-Ti) were divided into 2 groups, one group without plate molding and the other with plate molding to a dog femora bone. Thirty-six plates of different sizes (5.0, 6.5, 8.0, 9.0, 10.0 and 11.0-mm diameter) were divided into 6 groups containing 6 plates of each size and submitted to the 4-point flexion test of resistance, using a piece of dog femur (weights of 5, 10, 15, 20 and 25 kg) as the bone in which the molding was performed. The evaluations were tabulated and analyzed using the program GraphPad Prism version 5.0. Corrections of the normal distribution curve were made using the Bartlett test. After the corrections, one-way analysis of variance (ANOVA) was performed with P < 0.05. Assessments were made within the group and between groups. Subsequently, the Newman-Keuls test was performed, adopting P < 0.05. For analyses in 2 groups, Student’s t-test was performed as a post-test, also with P < 0.05. When the plates were compared between equal sizes of groups 1 and 2, the non-molded plate group (G1) obtained the best results in the flexural stiffness and structural flexion tests. However, in the flexural resistance test, most plates obtained similar results and the plates with diameters of 8 mm, 9 mm and 10 mm of the molded plate group (G2) obtained the best results. Discussion: Our results show that the implants had adequate mechanical characteristics, but the unmolded plates had greater flexural and structural stiffness than the molded plates. This difference was significant, thus demonstrating a large loss of stiffness in relation to the original conformation. However, when we tested the flexural resistance, no significant differences were observed, and although without significant statistical changes, there was an increase in the resistance of the plate with the new conformation obtained by molding. In the results of the mechanical tests, we observed that after the molding, the implants gained greater resistance, although the difference was not statistically significant. This suggests that the architecture of the implants should have slight curvature in the medial direction of the bone, since this would lead to a better adaptation to the anatomy of the bone, and possibly greater resistance, as indicated by the new configuration after molding. Keywords: bone implants, titanium, orthopedic implants, femur, dogs.